Brain Abscess at the Site of Recent Primary Intracerebral Hemorrhage - Faisal Memon; Vikram Londhey; Rani D. Meshram; Gautami M. Kolhe (Indian Journal of Medical Specialities)
Brain abscesses are rare and potentially lethal neurological lesions, requiring prompt attention. Although brain abscesses are known to complicate surgically intervened intracerebral hemorrhages (ICH), but the formation of a brain abscess at the site of an ICH treated without surgery is exceptional. We hereby report a case of a 14-year-old female presenting with a brain abscess 6 weeks after an episode of spontaneous ICH with no identifiable focus of infection. She was effectively treated with antibiotics in combination with craniotomy and excision of abscess and was discharged with good recovery.